Integrated municipal solid waste planning and management ( IMSWPM ) in developing countries : The Feasibility analysis of a Case Study in the Municipality of Bandung - Yudoko, Gatot (Jurnal Manajemen Teknologi, 2005)
This paper is the second of two parts. In this part, the results of the analysis and evaluation of the proposed framework on integrated municipal solid wastem planning and management (IMSWPM) in developing countries in the Municipality of Bandung are presented. Feasibility analysis for IMSWPM in was hindered by difficulties in quantifying benefits and requirements. In general, our analysis indicated that waste reduction initiatives will be feasible if strong political commitment from the government and funds for conducting public education are available. Source separation initiatives will be feasible if PDK-Bandung is willing to adapt its collection and transportation operation system in particular the collection vehicles. The scheme for employing both local community organizations and the municipal cleansing enterprise in service provision is feasible because it has been implemented and enforced by a municipal law. The feasibility of the proposed arrangement for sorting and recycling centres will be determined by the willingness of the municipal government of Kotamadya Bandung and PDK-Bandung to provide land and to acknowledge waste pickers’ involvement. The feasibility of composting initiatives at household, community and municipal levels will depend upon the availability of funds to create and develop markets for compost. Sanitary landfill as a safe disposal option is feasible if additional revenue can be provided for PDK-Bandung. The use of incineration, meanwhile, seems currently infeasible. The sustainability of IMSWPM in the City of Bandung will be determined by several critical factors, such as stakeholders’ agreement on the common interest(s) such as vision and mission, availability of sufficient resources ( experts, money, support) capability of stakeholders in overcoming barriers to the implementation of IMSWPM, availability of enforcement mechanisms, and existing opportunies for the adoption and implementation of IMSWPM.